Baseline systolic blood pressure and efficacy of dual antiplatelet in acute ischaemic stroke - Yue Wang (Stroke and Vascular Neurology)
Objective Systolic blood pressure (SBP) affects the risk of early neurological deterioration (END). This subgroup analysis of Antiplatelet Therapy in Acute Mild to Moderate Ischemic Stroke (ATAMIS) trial aimed to explore whether SBP at admission affected the efficacy of different antiplatelet therapies in preventing END.Methods Based on the modified intention-to-treat analysis set of the ATAMIS trial, patients were divided into two subgroups according to whether SBP at admission was equal to or higher than 140 mm Hg, which were further subdivided into clopidogrel plus aspirin and aspirin alone treatments according to the randomised assignment. We conducted multivariable regression analyses to detect relationship between SBP at admission and END, as well as efficacy of different antiplatelet therapies in each SBP subgroup. Primary endpoint was END defined as ≥2-point increase in 7-day National Institutes of Health Stroke Scale score. Safety endpoints included intracranial haemorrhage and bleeding events during the trial.Results This study included 2915 patients. Risk of END raised by 16% as SBP at admission increased by every 10 mm Hg (p<0.001). Clopidogrel plus aspirin resulted in significantly lower risk of END than aspirin alone in patients with SBP≥140 mm Hg (5.5% vs 7.9%; adjusted risk difference (RD) and 95% CI −2.5% (−4.1% to −1.0%)), but not in those with SBP<140 mm Hg (3.4% vs 4.2%; adjusted RD and 95% CI −0.8% (−3.2% to 1.7%)). Efficacy of different antiplatelet therapies and SBP did not show significant interaction (p=0.50). Safety endpoints were similar between treatments in SBP subgroups.Conclusion The risk of END increases with elevated SBP at admission among patients with acute mild-to-moderate ischaemic stroke who are not suitable for reperfusion treatments. Fewer END occurred following clopidogrel plus aspirin compared with aspirin alone across different SBP levels. The finding should be interpreted cautiously.